Apical extrusion of bacteria following the use of reciprocating single-file and rotary multi-file instrumentation systems in oval root canals - Kurnaz, Safa; Bag, Irem; Gulbandilar, Aysel (Brazilian Dental Science, 2020)
Objective: All instrumentation techniques and instruments are associated with apical extrusion during chemomechanical preparation, and this causes postoperative pain and flare-up. However, it is controversial whether reciprocal systems or rotary systems cause more apical extrusion. The objective of this in vitro study was to determine the differences in the amounts of apically extruded bacteria (AEB) associated with nickel-titanium rotary and reciprocating systems when used in oval-shaped root canals. Material and Methods: Seventy human mandibular premolar teeth with oval-shaped canals were randomly assigned to four experimental groups (15 teeth in each group) and one control group (10 teeth). The root canals were contaminated with Enterococcus faecalis and instrumented using two full-sequence rotary instruments (ProTaper Universal [PTU] and ProTaper Next [PTN]) and two reciprocating single-file instruments (Reciproc [R] and WaveOne [WO]). A 0.9% NaCl solution was used as an irrigant, and the bacterial extrusion was quantified as the number of colony-forming units for each sample. The results were statistically analyzed using the Kruskal-Wallis one-way analysis of variance and the Mann-Whitney U test, and the statistical significance level was set at p <0.05. Results: The R system was associated with the highest amount of bacterial extrusion (p <0.05). The PTU system caused more bacterial extrusion than the PTN and WO systems (p <0.05). There was no significant difference between the PTN and WO systems (p >0.05). Conclusions: All instrumentation techniques caused apical bacterial extrusion. The instrument design and preparation techniques affect the number of extruded bacteria. KEYWORDS Apical extrusion; Bacteria; Endodontics; Root canal preparation.